Peningkatan Kemandirian Desa Melalui Program Peduli Lingkungan dan Bimbingan Belajar - Farhan, Muhammad; Briliana, Fadilah; Kusumawati, Amanda Nur; Muhammad, Fajri Trias Fauzi; Ulinnuha, Moh. Fikri; Prasetio, Aji; Ningsih, Tri Agusti; Fitriani, Devi; Hasyanah, Siti Nur; Ungau, Yudhisthira Arya; Zaenuri, Muchamad (Universitas Muhammadiyah Yogyakarta, 2025)
Community Service Program (KKN) 056 in Bendorejo Hamlet, Semanu Subdistrict, Gunung Kidul Regency, Special Region of Yogyakarta, was implemented as an effort to empower the community through a series of educational and mentoring programs. mentoring programs. Bendorejo Hamlet has significant natural and human resource potential, but still faces challenges in potential, but still faces challenges in resource management and quality of life improvement. and improving the quality of life. The goal of this Program is to assist community in understanding and managing the potential of the Village more effectively. The program includes collecting monographic data of the Dukuh for mapping the profile and potential of the area. mapping the profile and potential of the area, so that it can be used as a basis for village development planning, magical education, and community development. in village development planning, maggot education as a solution to organic waste management as well as creating economic opportunities for the community, especially maggot farmers. creating economic opportunities for the community, especially poultry farmers, farming education and product samples to increase the added value of agricultural products by providing information on the value of agricultural products. increase the added value of agricultural products by providing information related to processing of farm products into products that have more economic value, tutoring to support the education of children to children's education to help them improve their academic understanding and foster their interest in learning. This program is expected to be a solution to the limited access to additional education in the area. to additional education in the area, as well as optimizing the empowerment of Jaga Warga to strengthen environmental security. neighborhood security. The methods used in this program include observation, socialization, hands-on practice, and group discussions that help them to improve their academic understanding